Brain Mechanisms Underlying Decision-Making: A Biological Perspective - Raza, Amna; Nadeem, Muqadas (Nepal Journal of Neuroscience, 2026)
Decision making plays a substantial role in our daily activities. The entire mechanism of perceiving, thinking and actively deciding is primarily controlled by neurology circuits. Recent studies in genetics, sociology and behavioural sciences has proven that environmental factors tend to influence our decisions indirectly by altering the neurological mechanisms.